The first characterization of cubic Nd3+-doped mixed La2MoWO9 in micro-crystalline powders and translucent micro-ceramics. Issue 27 (30th June 2022) - Wilk (Bieza), M.; Tomaszewicz, E.; Siczek, M.; Guyot, Y.; Boulon, G.; Guzik, M.
Abstract : Crystal structure of Nd 3+ -doped La2 MoWO9 new optical material was investigated and translucent optical ceramics were fabricated for the first time. Abstract : Herein, the structural and spectroscopic properties of a new optical material, cubic Nd 3+ -doped mixed molybdato-tungstate with the chemical formula La2 MoWO9, which could be employed to achieve the difficult task of fabricating transparent ceramics, were investigated. The samples in the form of micro-powders were obtained via solid-state reaction and the first translucent micro-ceramics were demonstrated. The previously studied micro-ceramics activated with Yb 3+ ions showed the segregation phenomenon of a second phase, which was very rich in Yb 3+ ions in the grain boundary, and thus a solution to avoid this phenomenon was sought. Currently, we are interested in the use of the Nd 3+ dopant for two reasons, i.e., laser application and its role as a structural probe. This element has an ionic radius closer to that of La 3+ than Yb 3+, and thus substitutes La 3+ better in the framework. Consequently, this was beneficial to obtain a more homogenous cubic mono-phase material, and in the next step, translucent ceramics. The fundamental analysis was conducted using complementary techniques such as XRD and TEM/SEM combined with low-temperature high-resolution spectroscopic techniques to elucidate the main features of this promising optical material. A few Nd 3+ non-equivalent symmetry sites were observed, in accordance with the crystallographic analysis. Lastly, we also showed that the spectroscopic properties of the Nd 3+ ion embedded in the La2 MoWO9 host lattice were correlated with its initially missing crystal structure, which was solved based on the single crystal selected from the micro-crystalline form and presented for the first time.